THE NEED TO DEVELOP METHODS OF USING ANCIENT PROBLEMS IN THE TEACHING OF MATHEMATICS - Yakubjonova Maftunakhan Islamjon Kizi; Madaminov Muzaffar Ma'rufjon o'g'li (Researchparks Publishing, 2023)
In this article, the influence of the development of methods of using ancient problems in the teaching of mathematics on mathematics education is based on the data obtained from scientific sources.